Effect of self-reported home smoking restriction on smoking initiation among adolescents in Taiwan: a prospective cohort study - Luh, Dih-Ling (BMJ Open, 2015)
OBJECTIVE: The aims of this study were to investigate the influence of home smoking restriction (HSR) and the modified effect of parental smoking on smoking initiation among adolescents. DESIGN: Prospective Cohort Study. SETTING: Junior high school in Keelung City, Taiwan. PARTICIPANTS: This study collected and evaluated primary data from the Adolescent Smoking and Other Health-Related Behaviour Survey conducted in Keelung City, which aimed to investigate smoking and health-related behaviours in junior high school students (2008–2009). Data on students free of smoking in 2008 and following them until 2009 (n=901) to ascertain whether they had started smoking were analysed with logistic regression mode to examine the proposed postulates. MAIN OUTCOME MEASURE: The outcome variable was smoking initiation, which was defined as smoking status (yes/no) in the 2009 follow-up questionnaire. The main independent variable was HSR obtained from an adolescent self-reported questionnaire. Information on parental smoking was measured by adolescents self-reporting the smoking behaviour of their father and mother. RESULTS: The rate of HSR was 29.79% among 7th grade adolescents. The effect of HSR on smoking initiation in adolescents was statistically significantly modified by paternal smoking (p=0.04) but not by maternal smoking (p=0.54). The effect of HSR on smoking initiation was small for fathers with the habit of smoking (OR=0.89, 95% CI (0.42 to 1.88)), but the corresponding effect size was 3.2-fold (OR=2.84, 95% CI 1.19 to 6.81) for fathers without the habit of smoking. CONCLUSIONS: Paternal smoking behaviour may play an interactive role with HSR in preventing smoking initiation among Taiwanese adolescents.